Rapid microwave assisted hydrothermal synthesis cerium vanadate nanoparticle and its photocatalytic and antibacterial studies. (February 2020) - Mishra, S.; Priyadarshinee, M.; Debnath, A.K.; Muthe, K.P.; Mallick, B.C.; Das, N.; Parhi, P.
Abstract: Catalyst or template-free synthesis of cerium orthovanadate (CeVO4 ) nanoparticles were synthesized by simple, fast and efficient microwave assisted hydrothermal method using Ce(NO3 )3 ·6H2 O and NaVO3 as the starting materials under basic pH condition. The prepared sample was characterized by powder X-ray diffraction (XRD) transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FTIR) and Uv–Visible diffuse reflectance spectroscopy (DRS). Pure tetragonal CeVO4 was successfully synthesized in 10 min of reaction time. The synthesized nanoparticles showed particle sizes in the range 10–20 nm and the optical absorption onset at 456 nm. The optical band gap was calculated to be 2.8 eV. The photocatalytic activity of the synthesized nanoparticles was evaluated by studying the degradation of a model dye, Eosin yellow (EY) under visible irradiation and a feasible mechanism was proposed. More than 89% of EY (60 mg/L) was degraded within 120 min. The antibacterial activity was also evaluated against Gram + ve and Gram -ve microbial pathogens. Graphical abstract: Image 1 Highlights: Tetragonal CeVO4 nanoparticles were synthesized for the first time by microwave mediated hydrothermal method. Photocatalytic activity of the cerium vanadate under visible light irradiation was evaluated. Antibacterial activity of CeVO4 against both Gram + Ve and Gram-Ve microbial pathogens has been studied.